Stone coating with high cohesiveness and preparation method thereof
By preparing modified polyurethane oligomers and combining other components, the problems of insufficient bonding and lack of antibacterial properties of traditional stone coatings are solved, and stone coatings with high bonding and antibacterial properties are achieved, meeting the multiple needs of stone protection.
Patent Information
- Application Number
- CN202411608026.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The bonding properties of traditional polyurethane coatings cannot meet the requirements of current stone coatings and lack antibacterial properties.
By preparing a modified polyurethane oligomer, combining polymethyl acrylate, reactive diluents and photoinitiators, a stone coating with high adhesion and antibacterial properties is formed.
It significantly improves the bonding performance, antibacterial properties and mechanical properties of stone coatings, meeting the multiple needs of stone protection.
Smart Images

Figure CN119490767A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a stone coating with high adhesion and a preparation method thereof. Background Art
[0002] Stone is one of the most widely used and oldest building materials in human history. It is widely used in building decoration materials, wall and other fields due to its rich resources, high compressive strength, durability, wear resistance and good decorative properties. However, due to damage from wind, rain and other factors, it will cause cracking, mildew, weathering and other problems, so the protection of stone is urgent.
[0003] At present, one of the ways to protect stone is to apply a layer of paint on its surface. Polyurethane paint is widely used in wood furniture, interior decoration and other fields due to its good adhesion and weather resistance. However, with the continuous upgrading of technology, the bonding performance of traditional polyurethane paint can no longer meet the requirements of stone paint at this stage. Therefore, it is necessary to improve the bonding performance of polyurethane paint.
[0004] For example, the patent with authorization announcement number CN 102140281 B discloses a coating for protecting the back of stone. The coating prepared by the invention is applied to the back of the stone and has good bonding properties and waterproof and alkali-proof effects, but does not improve the antibacterial properties of the stone coating. Summary of the invention
[0005] The purpose of the present invention is to provide a stone coating with high adhesion and a preparation method thereof, and to enhance the adhesion, antibacterial and mechanical properties of the stone coating by preparing a modified polyurethane oligomer.
[0006] The technical solution adopted by the present invention is:
[0007] A stone coating with high adhesion, the stone coating with high adhesion is composed of the following components in parts by weight:
[0008] 20-60 parts by weight of modified polyurethane oligomer, 10-30 parts by weight of polymethyl acrylate, 20-40 parts by weight of reactive diluent, and 2-10 parts by weight of photoinitiator;
[0009] The preparation method of the stone coating is:
[0010] The modified polyurethane oligomer and polymethyl acrylate are stirred and mixed uniformly, and then an active diluent and a photoinitiator are added thereto, stirred and dispersed, and allowed to stand to obtain a stone coating.
[0011] According to the above technical solution, preferably, the reactive diluent is one of butyl acrylate and tripropylene glycol diacrylate.
[0012] According to the above technical solution, in a preferred case, the photoinitiator is one of photoinitiator 184 and photoinitiator 1173.
[0013] According to the above technical solution, preferably, the preparation method of the modified polyurethane oligomer is:
[0014] (1) adding diallylamine and γ-mercaptopropyltriethoxysilane to a toluene solvent, stirring and dispersing, and then adding azobisisobutyronitrile thereto, reacting at 70-80° C. for 20-40 minutes, and after the reaction is completed, rotary evaporation is performed to obtain an intermediate 1;
[0015] (2) adding intermediate 1 and 1,2-epoxy-5-hexene to toluene solvent, stirring and dispersing, heating to 80-90° C., reacting for 2-5 hours, and after the reaction, distilling under reduced pressure and recrystallizing to obtain intermediate 2;
[0016] (3) Under a nitrogen atmosphere, intermediate 2 and (2-chloroethyl)benzene were added to an ethanol solvent, stirred and mixed evenly, and reacted at 100-120° C. for 12-24 h. After the reaction was completed, the intermediate was recrystallized and dried to obtain intermediate 3;
[0017] (4) Under a nitrogen atmosphere, 1,6-hexamethylene diisocyanate trimer is added to butyl acetate solvent, the temperature is raised to 45-60° C., intermediate 3, hydroquinone inhibitor, and dibutyltin dilaurate are added thereto, the temperature is continued to be raised to 65-75° C., the reaction is carried out for 3-6 hours, and after the reaction is completed, the mixture is cooled to room temperature and discharged to obtain a modified polyurethane oligomer.
[0018] According to the above technical solution, preferably, in (1), the mass ratio of diallylamine, γ-mercaptopropyltriethoxysilane and azobisisobutyronitrile is 1:4.8-5.4:0.005-0.01.
[0019] According to the above technical solution, preferably, in (2), the mass ratio of the intermediate 1 to 1,2-epoxy-5-hexene is 1:0.15-0.3.
[0020] According to the above technical solution, preferably, in (3), the mass ratio of the intermediate 2 to (2-chloroethyl)benzene is 1:0.2-0.4.
[0021] According to the above technical solution, preferably, in (4), the mass ratio of hexamethylene diisocyanate trimer to intermediate 3 is 1:1.5-2.
[0022] According to the above technical solution, preferably, in (4), the mass of the hydroquinone inhibitor is 0.02-0.06% of the total mass of the 1,6-hexamethylene diisocyanate trimer and the intermediate 3; the mass of the dibutyltin dilaurate is 0.04-0.08% of the total mass of the 1,6-hexamethylene diisocyanate trimer and the intermediate 3.
[0023] The beneficial effects of the present invention are:
[0024] The invention uses diallylamine and γ-mercaptopropyltriethoxysilane as raw materials, performs click reaction to obtain intermediate 1, performs epoxy ring opening with 1,2-epoxy-5-hexene to obtain intermediate 2, uses tertiary amine of intermediate 2 and (2-chloroethyl)benzene to perform quaternization reaction to obtain intermediate 3, uses hydroquinone as an inhibitor, dibutyltin dilaurate as a catalyst, uses intermediate 3 and 1,6-hexamethylene diisocyanate trimer as main raw materials, performs nucleophilic addition reaction to obtain low molecular weight trifunctional modified polyurethane oligomer, uses the oligomer as main resin, adds active diluent and the like into the oligomer, stirs evenly, and obtains stone coating.
[0025] The stone coating prepared by the present invention contains a large amount of siloxane structures, and the silanol groups formed after hydrolysis can undergo condensation reaction with the hydroxyl groups on the surface of the stone, thereby increasing the adhesion performance of the coating to the stone. In addition, the urethane bonds contained therein can react with the hydroxyl groups of the stone, further enhancing the adhesion performance of the coating to the stone.
[0026] The stone coating prepared by the present invention contains a positively charged quaternary ammonium salt structure, which can be adsorbed to the surface of negatively charged microorganisms through electrostatic attraction, combined with the phospholipid bilayer and other negatively charged substances in the cell plasma membrane, destroy the cell plasma membrane, cause the release of substances in the cell plasma, lead to cell death, and achieve an antibacterial effect. The stone coating prepared by the present invention has good bonding performance and antibacterial performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a reaction route for modifying polyurethane oligomers. DETAILED DESCRIPTION
[0028] The following is a further description of the high-adhesive stone coating and its preparation method of the present invention in combination with some specific embodiments. The specific embodiments are for further illustrating the present invention in detail, but do not limit the protection scope of the present invention.
[0029] Example 1
[0030] (1) 10 parts by weight of diallylamine and 48 parts of γ-mercaptopropyltriethoxysilane were added to a toluene solvent, stirred and dispersed, and then 0.05 parts of azobisisobutyronitrile was added thereto. The mixture was reacted at 75° C. for 30 minutes. After the reaction was completed, the mixture was rotary evaporated to obtain an intermediate 1.
[0031] (2) According to weight, 20 parts of intermediate 1 and 4 parts of 1,2-epoxy-5-hexene were added to toluene solvent, stirred and dispersed, heated to 80° C., and reacted for 5 hours. After the reaction was completed, the reaction was distilled under reduced pressure and recrystallized to obtain intermediate 2.
[0032] (3) Under a nitrogen atmosphere, 20 parts of intermediate 2 and 8 parts of (2-chloroethyl)benzene were added to an ethanol solvent, stirred and mixed evenly, and reacted at 100° C. for 24 hours. After the reaction was completed, the mixture was recrystallized and dried to obtain intermediate 3.
[0033] (4) Under a nitrogen atmosphere, 40 parts of 1,6-hexamethylene diisocyanate trimer were added to butyl acetate solvent, the temperature was raised to 45°C, 80 parts of intermediate 3, 0.07 parts of hydroquinone inhibitor, and 0.1 parts of dibutyltin dilaurate were added thereto, the temperature was continued to be raised to 70°C, and the reaction was carried out for 3 hours. After the reaction was completed, the mixture was cooled to room temperature and discharged to obtain a modified polyurethane oligomer.
[0034] (5) 20 parts of modified polyurethane oligomer and 30 parts of polymethyl acrylate are stirred and mixed uniformly, and then 40 parts of butyl acrylate active diluent and 10 parts of photoinitiator 184 are added thereto, stirred and dispersed, and allowed to stand to obtain a stone coating.
[0035] Example 2
[0036] (1) 10 parts by weight of diallylamine and 50 parts of γ-mercaptopropyltriethoxysilane were added to a toluene solvent, stirred and dispersed, and then 0.1 parts of azobisisobutyronitrile was added thereto. The mixture was reacted at 70° C. for 40 minutes. After the reaction was completed, the mixture was rotary evaporated to obtain an intermediate 1.
[0037] (2) According to weight, 20 parts of intermediate 1 and 5 parts of 1,2-epoxy-5-hexene were added to toluene solvent, stirred and dispersed, heated to 85° C., and reacted for 2 hours. After the reaction was completed, vacuum distillation and recrystallization were performed to obtain intermediate 2.
[0038] (3) Under a nitrogen atmosphere, 20 parts of intermediate 2 and 6 parts of (2-chloroethyl)benzene were added to an ethanol solvent, stirred and mixed evenly, and reacted at 110° C. for 24 hours. After the reaction was completed, the mixture was recrystallized and dried to obtain intermediate 3.
[0039] (4) Under a nitrogen atmosphere, 40 parts of 1,6-hexamethylene diisocyanate trimer were added to butyl acetate solvent, the temperature was raised to 50°C, 60 parts of intermediate 3, 0.02 parts of hydroquinone inhibitor, and 0.1 parts of dibutyltin dilaurate were added thereto, the temperature was continued to be raised to 65°C, and the reaction was carried out for 6 hours. After the reaction was completed, the mixture was cooled to room temperature and discharged to obtain a modified polyurethane oligomer.
[0040] (5) 30 parts of modified polyurethane oligomer and 20 parts of polymethyl acrylate are stirred and mixed uniformly, and then 40 parts of tripropylene glycol diacrylate active diluent and 10 parts of photoinitiator 184 are added thereto, stirred and dispersed, and allowed to stand to obtain a stone coating.
[0041] Example 3
[0042] (1) 10 parts by weight of diallylamine and 54 parts of γ-mercaptopropyltriethoxysilane were added to a toluene solvent, stirred and dispersed, and then 0.05 parts of azobisisobutyronitrile was added thereto. The mixture was reacted at 80° C. for 20 min. After the reaction was completed, the mixture was rotary evaporated to obtain an intermediate 1.
[0043] (2) According to weight, 20 parts of intermediate 1 and 3 parts of 1,2-epoxy-5-hexene were added to toluene solvent, stirred and dispersed, heated to 85° C., and reacted for 5 hours. After the reaction was completed, vacuum distillation and recrystallization were performed to obtain intermediate 2.
[0044] (3) Under a nitrogen atmosphere, 20 parts of intermediate 2 and 8 parts of (2-chloroethyl)benzene were added to an ethanol solvent, stirred and mixed evenly, and reacted at 100° C. for 24 hours. After the reaction was completed, the mixture was recrystallized and dried to obtain intermediate 3.
[0045] (4) Under a nitrogen atmosphere, 40 parts of 1,6-hexamethylene diisocyanate trimer were added to butyl acetate solvent, the temperature was raised to 60°C, 70 parts of intermediate 3, 0.05 parts of hydroquinone inhibitor, and 0.04 parts of dibutyltin dilaurate were added thereto, the temperature was continued to be raised to 75°C, and the reaction was carried out for 6 hours. After the reaction was completed, the mixture was cooled to room temperature and discharged to obtain a modified polyurethane oligomer.
[0046] (5) 40 parts of modified polyurethane oligomer and 10 parts of polymethyl acrylate are stirred and mixed uniformly, and then 40 parts of butyl acrylate active diluent and 10 parts of photoinitiator 1173 are added thereto, stirred and dispersed, and allowed to stand to obtain stone coating.
[0047] Example 4
[0048] (1) 10 parts by weight of diallylamine and 52 parts of γ-mercaptopropyltriethoxysilane were added to a toluene solvent, stirred and dispersed, and then 0.05 parts of azobisisobutyronitrile was added thereto. The mixture was reacted at 75° C. for 30 minutes. After the reaction was completed, the mixture was rotary evaporated to obtain an intermediate 1.
[0049] (2) According to weight, 20 parts of intermediate 1 and 4 parts of 1,2-epoxy-5-hexene were added to toluene solvent, stirred and dispersed, heated to 80° C., and reacted for 5 hours. After the reaction was completed, the reaction was distilled under reduced pressure and recrystallized to obtain intermediate 2.
[0050] (3) Under a nitrogen atmosphere, 20 parts of intermediate 2 and 6 parts of (2-chloroethyl)benzene were added to an ethanol solvent, stirred and mixed evenly, and reacted at 110° C. for 24 hours. After the reaction was completed, the mixture was recrystallized and dried to obtain intermediate 3.
[0051] (4) Under a nitrogen atmosphere, 40 parts of 1,6-hexamethylene diisocyanate trimer were added to butyl acetate solvent, the temperature was raised to 50°C, 70 parts of intermediate 3, 0.05 parts of hydroquinone inhibitor, and 0.1 parts of dibutyltin dilaurate were added thereto, the temperature was continued to be raised to 65°C, and the reaction was carried out for 6 hours. After the reaction was completed, the mixture was cooled to room temperature and discharged to obtain a modified polyurethane oligomer.
[0052] (5) 50 parts of modified polyurethane oligomer and 20 parts of polymethyl acrylate are stirred and mixed uniformly, and then 20 parts of tripropylene glycol diacrylate reactive diluent and 10 parts of photoinitiator 184 are added thereto, stirred and dispersed, and allowed to stand to obtain a stone coating.
[0053] Example 5
[0054] (1) 10 parts by weight of diallylamine and 48 parts of γ-mercaptopropyltriethoxysilane were added to a toluene solvent, stirred and dispersed, and then 0.1 parts of azobisisobutyronitrile was added thereto. The mixture was reacted at 75° C. for 30 minutes. After the reaction was completed, the mixture was rotary evaporated to obtain an intermediate 1.
[0055] (2) According to weight, 20 parts of intermediate 1 and 6 parts of 1,2-epoxy-5-hexene were added to toluene solvent, stirred and dispersed, heated to 90° C., and reacted for 2 hours. After the reaction was completed, the reaction was distilled under reduced pressure and recrystallized to obtain intermediate 2.
[0056] (3) Under a nitrogen atmosphere, 20 parts of intermediate 2 and 4 parts of (2-chloroethyl)benzene were added to an ethanol solvent, stirred and mixed evenly, and reacted at 120° C. for 12 h. After the reaction was completed, the mixture was recrystallized and dried to obtain intermediate 3.
[0057] (4) Under a nitrogen atmosphere, 40 parts of 1,6-hexamethylene diisocyanate trimer were added to butyl acetate solvent, the temperature was raised to 50° C., 70 parts of intermediate 3, 0.05 parts of hydroquinone inhibitor, and 0.05 parts of dibutyltin dilaurate were added thereto, the temperature was continued to be raised to 70° C., the reaction was carried out for 4 hours, and after the reaction was completed, the mixture was cooled to room temperature and discharged to obtain a modified polyurethane oligomer.
[0058] (5) 60 parts of modified polyurethane oligomer and 18 parts of polymethyl acrylate are stirred and mixed uniformly, and then 20 parts of tripropylene glycol diacrylate active diluent and 2 parts of photoinitiator 184 are added thereto, stirred and dispersed, and allowed to stand to obtain a stone coating.
[0059] Apply the stone paint on the clean stone surface, apply it evenly by roller coating, leave it for 5 minutes, and place it in a light curing machine to cure it into a film. The curing conditions are a 2KW high-pressure tribute lamp, a power density of 100W / cm2, and a curing time of 10s.
[0060] Refer to GB / T1720-1979 to measure the coating adhesion.
[0061] Refer to GB / T6739-2006 to test the coating hardness.
[0062] Refer to GB / T1732-1993 to test the impact resistance of the coating.
[0063] Table 1:
[0064]
[0065]
[0066] The higher the adhesion level, the better the bonding performance. It can be seen from the table that the coating prepared by the present invention has good bonding performance. It can be seen from the table that with the increase of modified polyurethane oligomers, the double bond content increases, the active groups increase, the cross-linking density increases, and the impact resistance increases. In addition, with the increase of rigid groups such as phenyl and six-membered rings in the polyurethane coating, its hardness increases.
[0067] Referring to HG / T3950-2007, the test microorganisms are Escherichia coli and Staphylococcus aureus.
[0068] Table 2:
[0069]
[0070] It can be seen from the table that the stone coating prepared by the present invention has good antibacterial performance, and the antibacterial rate can reach up to 99.9%.
[0071] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A stone coating with high adhesion, characterized in that: The high-adhesive stone coating is composed of the following components in parts by weight: 20-60 parts by weight of modified polyurethane oligomer, 10-30 parts by weight of polymethyl acrylate, 20-40 parts by weight of reactive diluent, and 2-10 parts by weight of photoinitiator; The preparation method of the stone coating is: The modified polyurethane oligomer and polymethyl acrylate are stirred and mixed uniformly, and then an active diluent and a photoinitiator are added thereto, stirred and dispersed, and allowed to stand to obtain a stone coating.
2. The stone coating with high adhesion according to claim 1, characterized in that: The active diluent is one of butyl acrylate and tripropylene glycol diacrylate.
3. The stone coating with high adhesion according to claim 1, characterized in that: The photoinitiator is one of photoinitiator 184 and photoinitiator 1173.
4. The stone coating with high adhesion according to claim 1, characterized in that: The preparation method of the modified polyurethane oligomer: (1) adding diallylamine and γ-mercaptopropyltriethoxysilane to a toluene solvent, stirring and dispersing, and then adding azobisisobutyronitrile thereto, reacting at 70-80° C. for 20-40 minutes, and after the reaction is completed, rotary evaporation is performed to obtain an intermediate 1; (2) adding intermediate 1 and 1,2-epoxy-5-hexene to toluene solvent, stirring and dispersing, heating to 80-90° C., reacting for 2-5 hours, and after the reaction, distilling under reduced pressure and recrystallizing to obtain intermediate 2; (3) Under a nitrogen atmosphere, intermediate 2 and (2-chloroethyl)benzene were added to an ethanol solvent, stirred and mixed evenly, and reacted at 100-120° C. for 12-24 h. After the reaction was completed, the intermediate was recrystallized and dried to obtain intermediate 3; (4) Under a nitrogen atmosphere, 1,6-hexamethylene diisocyanate trimer is added to butyl acetate solvent, the temperature is raised to 45-60° C., intermediate 3, hydroquinone inhibitor, and dibutyltin dilaurate are added thereto, the temperature is continued to be raised to 65-75° C., the reaction is carried out for 3-6 hours, and after the reaction is completed, the mixture is cooled to room temperature and discharged to obtain a modified polyurethane oligomer.
5. The stone coating with high adhesion according to claim 4, characterized in that: In the above (1), the mass ratio of diallylamine, γ-mercaptopropyltriethoxysilane and azobisisobutyronitrile is 1:4.8-5.4:0.005-0.
01.
6. The stone coating with high adhesion according to claim 4, characterized in that: In the above (2), the mass ratio of the intermediate 1 to 1,2-epoxy-5-hexene is 1:0.15-0.
3.
7. The stone coating with high adhesion according to claim 4, characterized in that: In the above (3), the mass ratio of the intermediate 2 to (2-chloroethyl)benzene is 1:0.2-0.
4.
8. The stone coating with high adhesion according to claim 4, characterized in that: In the above (4), the mass ratio of hexamethylene diisocyanate trimer to intermediate 3 is 1:1.5-2.
9. The stone coating with high adhesion according to claim 4, characterized in that: In the above (4), the mass of the hydroquinone polymerization inhibitor is 0.02-0.06% of the total mass of the 1,6-hexamethylene diisocyanate trimer and the intermediate 3; the mass of the dibutyltin dilaurate is 0.04-0.08% of the total mass of the 1,6-hexamethylene diisocyanate trimer and the intermediate 3.
Citation Information
Patent Citations
Coating for protecting back face of stone
CN102140281B
Preparation method for organosilicone positive ion waterborne polyurethane
CN104327238A
UV (ultraviolet) photocuring waterborne polyurethane primer for vehicles and preparation method of UV photocuring waterborne polyurethane primer
CN116606592A
Modified polyurethane primer and preparation method thereof
CN118185450A
Process for crystal coating of artificial marble having excellent wear resistance and high gloss
KR1020090125519A